Evolução da forma e encolhimento de um sistema gel durante a secagem por convecção forçada - Arrieche, Leonardo da Silva (Universidade Federal de São Carlos, 2003)
Knowledge of the shape evolution and shrinkage of a spherical gel system during drying by forced convection significantly enhances the understanding of this process under the vision of the transport phenomena. This work consists in the development of a gel system, with spherical geometry, which allows analyzing the effect of the fluid flow, in the boundary layer, on the moisture transport, shrinkage and on the shape evolution of the sample, during drying in an air stream forced convection equipment. The shrinkage was observed through the capture of images, used for the calculation of shape factors. The process was evaluated under a laminar flow (based on particle diameter), with a agar concentration of 1.5 and 3% (wet basis), fluid velocities varying from 1.0 to 2.0 m/s and initial particle diameters of 1.61.10-2 and 2.66.10-2 m, being the temperature maintained at 50 0C. The results confirmed with good reproducibility, proved statistically, that the circularity and specific mass of the samples decrease according to the formation of accentuated two-dimensional moisture profiles, for moisture contents lower than the critical value. The difference between the maximum and minimum diameters of a sample, during the process, evidenced the variation of the mass transfer rates between the previous and subsequent areas. It was inferred that during the constant drying rate period, the analysis is pondered in relation to the moisture transport, with the circularity and specific mass of the samples staying approximately constant. The gel system used allowed to reach the proposed objective, in a selective way, representing materials intensely affected by the shrinkage.
Keywords: Secagem; Encolhimento; Fatores de forma; Períodos de secagem; Camada limite; ENGENHARIAS::ENGENHARIA QUIMICA